Economic consequences of landlockedness - What makes a difference? - Guannan Miao; Andreas Wörgötter (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2021)
The economic disadvantage of landlocked countries is well established in the literature (Faye et al, 2004). This paper investigates the economicimpact of landlockedness on convergence. The econometric analysis is carried out for three income groups and the time before and after the global financial crisis (GFC) of 2007/9. The quality of institutions, investment rate, landlockedness, international trading costs and trade openness are used as conditional variables. The time period under investigation is 1996 to 2016. This paper contributes to the debate between geography (Sachs, 2003) and institutions (Rodrik et al, 2004) as main obstacles for higher economic growth in landlocked countries.
Keywords: 330